Stunting Prevention Movement Through Education Programs in Kumbang Village Community - Lensoni, Lensoni; Sakinah, Juliana (Transpublika Publisher, 2024)
Stunting is one of the main health problems in Indonesia that affects children's physical growth and cognitive development. To overcome this, increasing students' knowledge and awareness through educational activities about balanced nutrition is a strategic effort that can be implemented in the school environment. This research aims to measure the effectiveness of nutrition education activities at School 2 Lhoksukon in increasing students' knowledge about balanced nutrition and the importance of preventing stunting. Educational activities are carried out with an interactive approach involving lecture sessions, group discussions and direct practice regarding the selection and processing of nutritious food. The results of the analysis show a significant increase in the level of students' understanding of the concept of balanced nutrition, the importance of nutritious food, and the impact of stunting on health. Apart from that, there was a change in students' behavior in choosing healthier food after attending the education. In conclusion, this educational activity is effective in increasing students' knowledge and awareness about balanced nutrition and stunting prevention. Similar programs need to be expanded and implemented sustainably as part of the national strategy to reduce stunting rates in Indonesia.